EPISTEMOLOGI ILMU HUDHURI MULLA SHADRA - FATHUL MUFID (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2012)
Discussion on knowledge of hudhuri (knowledge by present) is an interesting topic in studying the history of philosophical thoughts or mysticism in Islam. Epistemologically, the knowledge of hudhuri is a farm of knowledge directly obtained by human from God, without involving the works of human's reasons conceptionally and human 's senses visually, but through involving the sanctity of human's soul (qalb). The criteria of the truth of this kind of knowledge is free from dualism between the truth and the mistakes. The concept of knowledge of hudhuri in the discourse of Islamic sciences has been explisitly formulated by Suhrawardi al-Maqtul, and then discussed by Mulla Shadrd. Before discussed by both Muslim thinkers, this concept has been also discussed by oleh al-Farabi, Ibn Sina, al-Ghazali, Ibn Rusyd, and Ibn 'Arabi by using different terms. Mulla Shadrd as a figure who Jives longest of the others, when he formulated the concept of knowledge of hudhuri, was possibly influenced by the previous concepts. Hence, it is so interesting to study it comprehensively and systematically. Key Words: Mulla Shadrd, Knowledge of hudhuri: epistemology, knowledge, and qalb.